Comparison of methods for isolating high quality genomic dna and total rna from the mycelia of an oil palm pathogen, Ganoderma boninense - Irene, L.I.; Abu Bakar, F.D.; Idris, A.S.; Murad, A.M.A (Penerbit Universiti Kebangsaan Malaysia, 2015)
Isolation of high quality and intact nucleic acids are important steps for a number of molecular techniques. The problems that are normally associated with nucleic acid isolation from filamentous fungi are the presence of high polysaccharide contaminants and tough cell walls. In this study, we compared several published protocols for efficient DNA and RNA isolation from the mycelia of an oil palm pathogen, Ganoderma boninense. Three protocols were analysed for the isolation of genomic DNA, with the best protocol being the hexacetyltrimethylammonium bromide (CTAB) method. This method yielded 336.5± 56.9 μg/ml genomic DNA from 0.1 gm of mycelia, with minimal carbohydrate contamination. This method also produced DNA of sufficient quality for PCR amplification of G. boninense DNA. A total of four protocols were analysed for RNA extraction. Among the four protocols, LiCl, SDS and phenol yielded the highest amount of total RNA, wherein a total of 359.83 ± 67.8 μg/ml total RNA from 0.1 gm of mycelia was obtained. Spectrophotometric assessment of the RNA indicated relatively high purity and an absence of carbohydrate contamination. This method produced RNA of sufficient quality that was suitable for RT-PCR of G. boninense genes.